2016
DOI: 10.1007/s13592-016-0474-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens, parasites, and parasitoids associated with bumble bees (Bombus spp.) from Uruguay

Abstract: As elsewhere in the world, bumble bees play a vital role as pollinators in Uruguay, but knowledge on their health status is still limited. Between September 2012 and May 2013, 403 adult individuals of the two species of Bombus known for the country (Bombus atratus , Bombus bellicosus) were collected in six localities. We found that 177 (119 B. atratus , 58 B. bellicosus) were harboring one or two types of pathogens, parasites, or parasitoids. Identification of these natural enemies carried out by morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
3
18
4
1
Order By: Relevance
“…Studies on regional scales report that pathogens also affect the abundance of bumble bees. Common reported pathogens of Bombus are trypanosomes and microsporidia, which are transmitted horizontally between bumble bee colonies and vertically within colonies [ 15 , 16 ]. In particular, the bumblebee Bombus terrestris and its parasite Crithidia bombi were studied extensively to determine the role of brood in disease transmission [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on regional scales report that pathogens also affect the abundance of bumble bees. Common reported pathogens of Bombus are trypanosomes and microsporidia, which are transmitted horizontally between bumble bee colonies and vertically within colonies [ 15 , 16 ]. In particular, the bumblebee Bombus terrestris and its parasite Crithidia bombi were studied extensively to determine the role of brood in disease transmission [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Un estudio reciente muestra una alta prevalencia del microsporidio Nosema ceranae en B. pauloensis y B. bellicosus (72% y 63%, respectivamente) (Arbulo et al, 2015). Este microsporidio se ha encontrado en varias especies de abejorros (Plischuk et al, 2009(Plischuk et al, , 2017Li et al, 2012;Graystock et al, 2013;Fürst et al, 2014) y en el caso de B. terrestris, aparece como muy virulento afectando la supervivencia de los insectos (Graystock et al, 2013). También se identificaron en especímenes de Uruguay de B. pauloensis varios virus que aparecen frecuentemente en las abejas melíferas como el BQCV (Black queens cell virus), DWV (Deformed wing virus), ABPV (Acute bee paralysis virus) y el SBV (Sacbrood virus) (Salvarrey, datos no publicados).…”
Section: Discusión Y Conclusionesunclassified
“…Previous studies reported the presence of internal and external parasites in queens, workers and males of both species, including the microsporidia N . ceranae [ 16 , 41 ] and Tubulinosema pampeana Plischuk et al, the nematode Sphaerularia bombi Dufour, one species of parasitoid diptera [ 41 ], and the external mites, Kuzinia spp. Zachvatkin, Pneumolaelaps longanalis Hunter and Husband, Pneumolaelaps longipilus Hunter, Scutacarus acarorum Goeze, and Tyrophagus putrescentiae Schrank [ 42 ].…”
Section: Introductionmentioning
confidence: 99%